Peran Desain Pembelajaran Dalam Pengembangan Moral Anak Didik - Muhamad Fatih Rusydi Syadzili (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
This article explore moral education, learning system based on educational institutions. Students have different style from each other, so moral development in the design of learning is very important for teachers. Cause the development of learning design is related to students’ morals, sudent be able to become a make changes as a whole, and bring changes to individual students.The design of moral learning is a system for the development of education and training programs. This learning system will make students have good morals in the bad behavior on society. Learning system must make teacher be a good person, cause learning system must make actual learning, not only focused on the substance of teaching material, but more strived to internalize the values of the teaching material.